ANALISIS DASAR PERTIMBANGAN HAKIM DALAM PENGAJUAN TUNTUTAN KEKURANGAN PEMBAYARAN UPAH MINIMUM PEKERJA (STUDI PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 195/Pdt.Sus-PHI/2016/PN.Bdg JUNCTO PUTUSAN MAHKAMAH AGUNG NOMOR 885K/Pdt.Sus-PHI/2017) - Sandra Angelica; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2019)
The demand for the minimum payment of the minimum wage has an expiration date, which is 2 years. The expiration date has been revoked with the Decision of the Constitutional Court Number 100/PUU-X/2012. In the Decision of the Industrial Relations Court Number 195/Pdt.Sus-PHI/2016/PN.Bdg juncto Decision of the Supreme Court Number 885K/Pdt.Sus-PHI/2017, the judge refused to grant the claim the minimum wage payment. Based on the verdict, what will be discussed in this paper are how the judges basis for filing a claim lacks payment of workers' minimum wages and how the legal consequences from the judge's consideration in filing a claim lack the minimum wage payment in the Industrial Relations Court Decision Number 195/Pdt.Sus-PHI/2016/PN.Bdg juncto Decision of the Supreme Court Number 885K/Pdt.Sus-PHI/2017. The research method used is normative legal research. Based on the research that has been done, the judge mistakenly interpreted the enactment of the Constitutional Court Decision Number 100/PUU-X/2012 so the judge refused to grant the claim for the lack of minimum wage payments submitted by the plaintiffs. The judge's judgment stated that the Constitutional Court Decision Number 100/PUU-X/2012 did not apply retroactively so that the normative rights expiration provisions last took effect on September 18, 2013. Even though the claim should have been partially granted by the judge because the employer proved to pay workers' wages under the minimum wage provisions applicable, namely for payment of wages in 2013. In addition, the plaintiffs also submitted the claim after the issuance of the Constitutional Court Decision Number 100/PUU-X/2012.